INTEGRASI NILAI ISLAMI DAN BUDAYA ACEH BERDASARKAN KURIKULUM KARAKTER - bt Yusoff, Nurahimah; Awang, Mohd Isha; Ibrahim, Ibrahim (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2014)
Indonesia covers a wide area that is usually called ‘dari Sabang sampai Merauke’ (from Sabang in westernmost point to Merauke to easternmost point) as mentioned in lyrics of a national folk song sang by students from elementary to high school. In its thousand islands live communities speaking various languages, living different cultures, characters and traditions that have become ethnical identities. The education and culture in a community are implemented from older to younger generations within a wide range of time and preserved well by the descendants. Indonesian characters are identical with oriental culture where people usually live in groups, mutual cooperation (‘gotong royong’), helpful and religious. Religion, education, culture, and tradition become basic norms is human society that have to be preserved and improved by individual, family, communities, and government to live peacefully. Aceh province, who has implemented Islamic law called sharia since a decade ago, have various art performances, languages, folk dance, traditional costume, and traditional foods that represent Aceh Islamic tradition that is harmonious with its slogan Mecca’s Veranda (Serambi Mekkah). The effort to implement character’s based curriculum in all schools in Aceh is a good chance to raise children to become adult that have moral ground and intelligent who understand technology and faith in facing globalization. By integrating religious and traditional values in education, we are expecting the students to have those good life skills in living social life in Islamic way.Key words: integration of values, Aceh, characters’ based curriculum